2006
DOI: 10.1017/s103507720001110x
|View full text |Cite
|
Sign up to set email alerts
|

Taking account of the ‘to and fro’ of children’s experiences in family law

Abstract: This paper outlines the possibilities and tensions that emerge in legal and social discourse when popular images and narratives of children as 'at risk' are juxtaposed with more revised constructions of the child as capable and autonomous. The paper explores this shift in representation of children against a background of extensive family law reform currently under way in Australia. It then reports insights from a pilot study which found that children 'to and fro' between accounts of hurt and powerlessness ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
(12 reference statements)
1
25
0
1
Order By: Relevance
“…74 Notably, children in our FRC study who had participated in child consultations also reported that they did not feel heard. Brooke's comments are illustrative: 69 Graham and Fitzgerald (2006); Fitzgerald and Graham (2010); Graham and Fitzgerald (2010). Parkinson and Cashmore (2008).…”
Section: Children Have Little Say or Access To Informationmentioning
confidence: 99%
“…74 Notably, children in our FRC study who had participated in child consultations also reported that they did not feel heard. Brooke's comments are illustrative: 69 Graham and Fitzgerald (2006); Fitzgerald and Graham (2010); Graham and Fitzgerald (2010). Parkinson and Cashmore (2008).…”
Section: Children Have Little Say or Access To Informationmentioning
confidence: 99%
“…Consistent with the definitions offered above, such authors term the ensuing adjustment process to be symptomatic of a grief response or a grieving process. Furthermore, and specific to children, the literature frequently cites that much of what we witness in the adjustment of children following separation such as sadness, anger, confusion and guilt for example, (Bagshaw, 1998 ;Graham, 2004;Hetherington & Clingempeel, 1992;McIntosh, 2003;Worden, 1996) can be thought of as emotional responses consistent with a grief response (Graham, 2004;Graham & Fitzgerald, 2006;Worden, 1996). Therefore, the linking of loss and separation, as this thesis does, is not in itself a new idea.…”
Section: Discussionmentioning
confidence: 99%
“…argued that this was a fear-based response resulting from the growing belief that children would be severely impacted in the long-term by trends of family breakdowns. What has ensued, over five decades of research into the impact of separation on children, is a vast literature that is, at times, both conflicted (Ahrons, 2006;Graham & Fitzgerald, 2006), and lacking consensus as to the extent or nature of the deleterious effects of separation on children (Demo & Fine, 2010). …”
mentioning
confidence: 99%
See 2 more Smart Citations